The impact of financial literacy and psychological factors on investment intention among a private university in Kampar, Malaysia - Wee, Woon Kai; Chua, Xiao Qing; Tee, Yu Xun; Wong, Jing En (2024)
This research aims to identify the investment intention among a private university in Kampar, Malaysia by referring Theory of Planned Behaviour, Information Cascade Theory and Prospect Theory. The independent variables included are financial knowledge, financial attitude, overconfidence, herding behaviour and loss aversion. The data collection method in this study is primary data and 384 sets survey questionnaires were collected. Statistical Package for Social Sciences 29.0 (SPSS 29.0) software was used to generate statistical analysis. The results showed that financial knowledge, financial attitude, herding behaviour and loss aversion have significant relationship with the investment intention among a private university in Kampar, Malaysia; while overconfidence has insignificant relationship with the investment intention among a private university in Kampar, Malaysia. This research will provide an insight for investors, Malaysia enlisted companies’ management to better understand the factors that will affect investment intention.